Study on Prevalence and Antimicrobial Susceptibility Patterns of Clinical Isolates in a Tertiary Care Teaching Hospital - Sriram, Shanmugam; C, Ashmi; Martin, Mercy Grow; Moorthy, Nanthini; Karthikeyan, Nivedha; Kumar, Preetha (Asian Journal of Biological and Life Sciences)
Context: Antimicrobial resistance is currently the most significant challenge to effectively treating infections globally. The threat of antibiotic resistance is growing at an alarming rate in developing countries, perhaps more rapidly. Aim: This study aims to determine the susceptibility patterns of micro-organisms to antibiotics and the prevalence of micro-organisms among common pathogens in a tertiary care hospital. Materials and Methods: The study was carried out in three phases. A retrospective study (first phase) was conducted for one year (January 2020-December 2020), and a prospective study (second phase) was performed for six months (April 2021-October 2021) in the inpatient department of General Medicine and Surgery on the sensitivity pattern of micro-organisms and in the third phase, obtained data’s from both the studies were compared and analysed. Results: A total of 980 cases were analysed in the first phase, in which majorly identified micro-organisms were E. coli (35.1%), Klebsiella (24.6%), and S. aureus (6.73%). During the second phase, 84 cases indicated that E. coli (30.9%) was highly sensitive to Imipenem, meropenem, and amikacin and showed higher cephalosporin resistance. In the third phase, comparing the data obtained from these studies revealed that the sensitivity pattern of E. coli to Piperacillin/tazobactam and meropenem has decreased from 26.9% to 9.5% and 29.7% to 17.5%. The sensitivity pattern of MSSA to Doxycycline and gentamicin increased from 1.1% to 3.2%. On the contrary, the sensitivity of MRSA to ofloxacin and gentamicin has decreased from 2% to 0% and 1.2% to 0%, respectively. Also, Klebsiella’s prevalence has increased from 18.6% to 26.2%, and E. coli has decreased from 33.2% to 30.9%. Conclusion: From the study, most clinical microorganisms have developed resistance against ofloxacin antibiotics compared to other antibiotics.
Keywords: Antibiotics; Antimicrobial resistance; Comparative Study; Prevalence.; Surgical site Infections